Infuence Of Mass Transfer Towards Pilot-Scale Semi-Continuous Cultivation Of Chlorella Vulgaris - Gek, Khoo Choon (2020)
Microalgae, well-known for their prominent photosynthetic efficiency and rapid growth rate emerge as a great feedstock for bio-energy production of third-generation biofuel. In this study, Chlorella vulgaris was chosen as the subject of investigation. The aim was to maximize the biomass production by investigating both the kinetic and mass transfer phenomena in a pilot-scale bubble column photobioreactor (BC-PBR) cultivation system. To account for the maximum microalgal biomass accumulation, the microalgae growth condition was optimized in the semi-continuous cultivation mode. Each cultivation cycle was carried out with 15 days of batch cultivation mode, followed by 3 cycles of 5 days each during semi-continuous cultivation mode. One-factor-at-a-time (OFAT) method was employed to investigate the effects of inoculum concentration of microalgae cells, photoperiod, and aeration rate towards microalgal growth performance, in the range of 0.1 – 0.35 g L-1, 12 and 24 h, and 0.12 – 0.19 vvm, respectively. The underlying mass transfer mechanism between gaseous CO2 and the culture medium were investigated under the optimized growth conditions. In addition, the reusability of the recycled water from the harvesting process was evaluated. To convert the microalgae into application biofuel, the harvested microalgal biomass was then converted into hydrochar via hydrothermal carbonization (HTC) reaction. The effects of hydrothermal temperature and retention time and the properties of hydrochar were studied at the range of 180 – 250 oC and 0.5 – 4 h, respectively. The research results showed that the optimum biomass accumulation was at 0.9819 g L-1, with cultivation conditions of: inoculum concentration of 0.3 g L-1, exposed under continuous (24 h) illumination with light intensity 60 – 70 μmol m-2 s-1, and supplied with compressed air at aeration rate of 0.16 vvm. The cultivation system underwent a bubble breakup mechanism during the transportation of gaseous CO2 into the culture medium with gas-liquid mass transfer coefficient, kLaL(CO2) of 0.45 s-1. Higher CO2 concentration environment did not affect the biomass accumulation due to the solubility limitation of CO2 in the microalgae culture. Based on optimized growth conditions for microalgae, a mathematical model for microalgae growth was developed. By incorporating the mass transfer parameter into the modified growth model, which was validated through an extended 120 days (21 cycles) of semi-continuous cultivation. In addition, the microalgae cells were proven to be able to grow in the recycled harvesting water. On the other hand, the highest energy yield of hydrochar was achieved at 76.59%, at the HTC under 210 oC for 0.5 h. Comparatively, higher heating value (HHV) of hydrochar produced was measured to be 24.51 kJ g-1, which is higher than that of raw biomass (12.58 kJ g-1). Moreover, the HTC process produced an aqueous phase that could be used as an alternative nutrient source for microalgae cultivation, yielding an average biomass accumulation of 0.8483 g L-1, demonstrating the feasibility of close loop cultivation. To conclude, mass transfer was a dominant factor affecting the kinetic growth of microalgae in pilot-scale semi-continuous BC-PBR cultivation system. It further affected the quality of produced biomass, and thus affected the downstream processing route chosen for optimal conversion of bioenergy.